Peran Pemerintah Desa Dalam Upaya Penanggulangan Pengganguran DI Desa Pliken, Kecamatan Kembaran, Kabupaten Banyumas - Sari, Indrianti Dwi Erlita; Agnestika, Indy; Anggraeni, Oki; Rahajuni, Dijan (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2025)
This study examines efforts to address unemployment in Pliken Village, Kembaran District, Banyumas Regency. Unemployment is one of the social problems that has broad impacts on community life, both economically and psychologically. This research employed a descriptive qualitative approach, conducted through in-depth interviews with the Village Head and the Head of the Service Section as the main informants. The results show that the village government has implemented various community empowerment programs, including skills training, the establishment of MSME associations, the organization of joint markets, and collaboration with regional government agencies. These programs are considered effective in creating new job opportunities, increasing community income, and significantly reducing the unemployment rate. The main obstacles faced are limited budget allocations and the prioritization of poverty alleviation programs for the elderly. Therefore, a strategic approach to sustainable village economic development is required, based on local potential and the strengthening of institutions such as Village-Owned Enterprises (BUMDes) and village cooperatives. The findings emphasize the importance of the active role of the village government in building an independent and adaptive economic ecosystem as a long-term solution to unemployment problems.